A review study on eye-tracking technology usage in immersive virtual reality learning environments. (April 2023) - Shadiev, Rustam; Li, Dandan
Abstract: This systematic review study synthesizes research findings pertaining to the use of eye-tracking technology in immersive virtual reality (IVR) learning environments created by using head mounted displays. Research published between January 2012 and May 2022 has been explored and specific inclusion and exclusion criteria have been applied to select articles. Fifty articles were selected and then reviewed with respect to (1) devices employed in research; (2) learning domains; (3) the number and academic level of participants, data collection methods, and duration of IVR activities; and (4) indicators and themes of visual attention. The main findings from this review demonstrate Tobii and HTC Vive are the most popular tools in research on eye-tracking technology usage in IVR learning environments. What's more, cognitive science and educational technology were found to be the most frequent domains in research on eye-tracking technology usage in IVR. The number of participants varied across reviewed articles but tertiary education was the most common academic level of participating students. Scholars used questionnaires and tests frequently to collect their research data. Fixation duration was the most frequently used indicator. The most frequent themes in reviewed research were task performance, teaching and learning strategies, and learning tools. The study concludes with suggestions for future research. Highlights: We reviewed thirty-six articles on eye-tracking technology in IVR. Our focus was on devices, domains, methods, indicators and themes in research. Future research directions were also provided.